Unilateral vs. bilateral DLPFC rTMS: comparative effects on depression, visual-spatial memory, inhibitory control and cognitive flexibility in major depressive disorder - Asgharian Asl, Fatemeh; Abbaszade, Sajjad; Derakhshani, Horeyeh; Vaghef, Ladan; Asgharian Asl, Amirreza (Frontiers in Psychiatry, 2024)
Background: Exciting left DLPFC activity with high frequency and inhibiting right DLPFC with low frequency repetitive transcranial magnetic stimulation (rTMS) has shown antidepressant effects in major depressive disorder (MDD) and executive functions. However, few studies have directly compared unilateral and bilateral protocols. Methods: Forty-seven individuals with treatment-resistant MDD underwent 10 sessions of rTMS over left DLPFC (20 Hz), bilateral DLPFC (left 20 Hz, right 1 Hz), or sham stimulation. Outcomes were depression (Beck Depression Inventory-II), visual-spatial memory (Corsi Block Test), response inhibition (Go/No-Go task), and cognitive flexibility (Wisconsin Card Sorting Test) assessed before and after treatment.Results: Both unilateral and bilateral rTMS significantly reduced depression levels versus sham controls based on BDI-II scores. While bilateral stimulation did not improve Corsi Test performance, unilateral protocol enhanced visual-spatial memory. On the Go/No-Go task, accuracy was higher in both active stimulation groups compared to sham, with no response time differences. Neither unilateral nor bilateral rTMS had significant effects on cognitive flexibility per the WCST.Conclusions: Despite comparable antidepressant effects, unilateral stimulation had some cognitive advantages over bilateral rTMS, potentially due to greater left dorsolateral prefrontal cortex excitation. Further research on parameter optimization is warranted.